Mediatory effects of quality of life on the relationship between lifestyle and marital satisfaction among employed women - Rajabi, Fahime; Khodabandelou, Rohollah (Social Determinants of Health, 2018)
Background: Marital satisfaction has been identified as one of the most important determinants of healthy and quality functions of family life. The present study aimed at examining the mediatory effects of quality of life in the relationship between lifestyle and marital satisfaction among employed women. Methods: In the context of a cross-sectional study, 120 married employed women were studied in Abadeh, Iran. Lifestyle Questionnaire (LSQ) including 70 items was used to evaluate different aspects of participant’s lifestyle. The Short Form Health Survey (SF-36) questionnaire was used to assess the health-related quality of life. Also, ENRICH Marital Satisfaction Questionnaire, including 35 items, was used to examine marital satisfaction. Data analysis was done using IBM SPSS Statistics for Windows, Version 24.0., running Pearson’s correlation coefficient, and Structural Equation Modelling using AMOS. Results The mean age of participants was 38.9 (9.84). Also, 58% (70) of participants had a bachelor’s degree, 36 (30%) had associate degrees, and 14 (12%) had masters and above. The results showed that there was a significant relationship between lifestyle and quality of life (r=0.061 and P<0.001). Also, there was a correlation between lifestyle and marital satisfaction (r=0.039 and P<0.001), and a significant relationship between quality of life and marital satisfaction (r=0.058 and P<0.001). It was also found that the quality of life partially mediates the relationship between lifestyle and marital satisfaction (β=0.32, P<0.001). Conclusion: Lifestyle based on cooperation and common goals leads to a life of marital satisfaction. By modifying their lifestyle, married employed women can amend their selfish tendencies and choose goals with high social orientation.